Harmonization of Sustainable Tourism Development Policy in the Regional Autonomy Era - Mashuril Anwar; Dinda Anna Zatika; Besti Lilyana (Journal of Law, Politic and Humanities, 2024)
Tourism development policies in the current era of decentralization have begun to be regulated in various legal instruments of regional autonomy. However, there is still substantial disharmony between the tourism development policies of the central government and regional governments. Consequently, there is an overlapping of policies and the emergence of sectoral egos that cause the development of the tourism sector to become unsustainable. This study aims to analyze the dynamics of the legal politics of tourism development in the regional autonomy regime, as well as to find a model of harmonization of the legal politics of sustainable tourism development in the regional autonomy regime. This study uses a doctrinal legal research method by examining the doctrine, legal principles, theories, and legal rules of tourism development and regional autonomy in Indonesia. Data processing is done through examination, classification, and systematization of legal materials. Furthermore, the data is analyzed descriptively-analytically. The results of the study indicate that the legal politics of tourism development in the regional autonomy regime have not fully reflected the legal politics of tourism development based on sustainability. Regions are given the authority to organize affairs in the tourism sector.